Using Application Based on Smartphone Android “Hello English” To Increase Students’ English Competency - Syamsiah Depalina Siregar; Siti Meutia Sari; Diena Fitria Simamora (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2020)
This research was conducted in increasing the students’ English comprehension. They are not English department the students. The using of Hello English Application Based on Android Smartphone available in online or offline, the students can use it in everywhere. The research use action research. Plans made such as the use of Android-based Hello English Application and research instruments as learning support. This action research starts from planning, acting, reflecting and evaluating. It consists of six meetings with 3 cycles. The implementation of learning goes well with starting activities, core activities (introduction and use of Hello English Application(and closing activities (giving posttest question). The first cycle, the students still confused with the app, it might them got low score. At the second cycle, the researcher gave the video tutorial about the app, therefore the students more relax and they got good score. In the third cycle, the students enjoyed with the app and got better score and brave follow the online match in the app. The result showed that there is improvement on the students’ comprehension with English in every meeting. This showed that the use of Hello English Application has an effect of increasing the students’ competency in learning English.